The Role of Socioeconomic Factors Contributed to The Prevalence of Children under Five Years Old with Small Stature in Jatinangor - Anggie Indari; Elsa Pudji Setiawati; Rodman Tarigan (Althea Medical Journal, 2015)
Background: Indonesia is on the fifth in world population for children with small stature. It could affect to their future, so growth disorders should be detected as early as possible. The influence of growth disorders is inseparable from the socioeconomic condition of the family. This study aims to analyze the influence of socioeconomic based on education, occupation and family income towards small stature children under five years old in Jatinangor.